Hubungan Antara Umur dan Jenis Kelamin dengan Kualitas Hidup Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis - Pius A. L. Berek; Yoakim Lay Un Fun Dales; Maria Fatimah W. A. Fouk (Pusat riset dan Inovasi Nasional, 2025)
Hemodialysis (HD) is the main therapy for end-stage chronic kidney failure (CKF) patients. Various factors, including age and gender, influence HD patients' quality of life (QoL). Studies on the relationship between these two factors and the QoL of HD patients in the RI-RDTL border area are still limited. This study aims to analyze the relationship between age and gender and HD patients' quality of life at Mgr. Gabriel Manek Hospital, SVD Atambua. This study used an observational analytical design with a cross-sectional approach. The study sample consisted of 50 HD patients who met the inclusion and exclusion criteria. QoL was measured using the WHOQoL instrument, and data were analyzed using the chi-square statistical test. The results showed no significant relationship between age and the quality of life of HD patients (p = 0.245). In addition, gender also had no significant relationship with the quality of life of HD patients (p = 0.643). Age and gender were not significantly related to the quality of life of HD patients. Other more influential factors need to be studied further to improve the quality of life of HD patients.